Utilization of Liposuction for Delayed Morel-Lavallée Lesion: A Case Report and Review - Preston Gardner; Diana Flis; Kongkrit Chaiyasate (Case Reports in Surgery)
Morel-Lavallée lesions are irregularly occurring and often overlooked results of traumatic injuries, resulting in potential long-term encapsulation of fluid between soft-tissue layers. The objective in this review was to discuss the delayed presentation of a Morel-Lavallée lesion and operative utility of liposuction in the patient’s treatment and review literature with particular focus on diagnosis and therapeutic interventions. The reviewed case demonstrates the presentation and successful therapy of a young female presenting with a MLL and contour deformity.